Symbiosis of Government and Market The private, the public and bureaucracy - Sadao Tamura, Minoru Tokita (RoutledgeCurzon, 2004)
In the twentieth century, the development of the principles of modern science and technology led to the flowering of material enlightenment. Human beings were broken down into details, only to be analysed and dealt with as objects. We know this has brought about the advancement of material enlightenment and a critical situation in the existence of human beings. At the beginning of the twenty-first century, these realities are beginning to be taken seriously on a global level. In many research fields, there is a demand for a new theory with human beings at its centre and based on observation of human beings as a whole, to be implemented in such a way that it will include modern scientific methods as well. This idea is called holism (a way of thinking based on a theory of the whole). We can find this in the philosophy of symbiosis, which has been practised and accumulated for years in the Community Well-being Development in the Oita region of Japan. We think of symbiosis as ‘taking opposite or different things and fusing them, integrating them, and having them reside together, emphasizing their respective benefits’. The topic of this book, arising from the symposium on the symbiosis of government and market, is based on the philosophy of symbiosis, a theory which has been developed and implemented with human beings at its centre, based on observation of human beings as a whole. This philosophy of symbiosis allows for the fusion of the principles of modern science and holism. Looking at symbiosis as a social system also makes possible the fusion of the economic ideologies of capitalism and socialism, resolving religious, cultural, ethnic, racial and north–south conflicts, as well as bridging the gap between generations. Originating in the observations based on the multi-channel medical system in the Oita region of southern Japan, the philosophy of symbiosis was developed through practical testing and logical positivism. This tradition has its roots in Dr. Hajime Sugita’s philosophy of the value of positive health. Whereas ‘horizontal symbiosis’ refers to individuals, families, companies, administrations and non-profit organizations, ‘vertical symbiosis’ refers to individuals, families, regions, nations and the earth. To balance these two levels of symbiosis, those who are creating a system are required sympathy (i.e. take other people’s wishes into account). Such a balance could be promoted through the education and study of a concept of health focusing on the idea of death. The horizontal and vertical symbioses could help both governments and markets to succeed, and contribute to the emergence of a society characterized by role multiplication.